Production of 21Ne in depth-profiled olivine from a 54 Ma basalt sequence, Eastern Highlands (37° S), Australia. (1st January 2018) - Matchan, Erin L.; Honda, Masahiko; Barrows, Timothy T.; Phillips, David; Chivas, Allan R.; Fifield, L. Keith; Fabel, Derek
Abstract: In this study we investigate the cosmogenic neon component in olivine samples from a vertical profile in order to quantify muogenic 21 Ne production in this mineral. Samples were collected from an 11 m thick Eocene basalt profile in the Eastern Highlands of southeastern Australia. An eruption age of 54.15 ± 0.36 Ma (2σ) was determined from 40 Ar/ 39 Ar step-heating experiments ( n = 6) on three whole-rock samples. A 36 Cl profile on the section indicated an apparent steady state erosion rate of 4.7 ± 0.5 m Ma −1 . The eruption age was used to calculate in situ produced radiogenic 4 He and nucleogenic 3 He and 21 Ne concentrations in olivine. Olivine mineral separates ( n = 4), extracted from the upper two metres of the studied profile, reveal cosmogenic 21 Ne concentrations that attenuate exponentially with depth. However, olivine (Fo68 ) extracted from below 2 m does not contain discernible 21 Ne aside from magmatic and nucleogenic components, with the exception of one sample that apparently contained equal proportions of nucleogenic and muogenic neon. Modelling results suggest a muogenic neon sea-level high-latitude production rate of 0.02 ± 0.04 to 0.9 ± 1.3 atoms g −1 a −1 (1σ), or <2.5% of spallogenic cosmogenic 21 Ne production at Earth's surface. These data support a key implicit assumption in the literature that accumulation of muogenic 21 Ne in olivine in surface samples is likely to be negligible/minimal compared to spallogenic 21 Ne.